Pulmonary artery catheter knotting: are conservative measures always successful? a case report - Sharma, Ashish; Singhal, Sushil Kumar; Grover, Vijay; Gupta, Vijay (International Surgery Journal, 2016)
Pulmonary artery catheter (PAC) or Swan-Ganz catheter is a flow directed balloon tipped catheter routinely used in patients undergoing Coronary Artery Bypass Grafting (CABG). The reported rate of complications with PAC is 3-17% including arrhythmias, pneumothorax, pulmonary embolism, bacteraemia and death1. Knot formation is an uncommon complication of PAC and is usually managed conservatively2. Here we report about a patient with knotted PAC who required operative intervention after failure of conventional measures as the knot engulfed the tricuspid valve chordae and was fixed.